The Protective Role of the Heme Catabolic Pathway in Hepatic Disorders - Vítek, Libor (Antioxidants & redox signaling, 2021)
Significance: As the central metabolic organ, the liver is exposed to a variety of potentially cytotoxic, proinflammatory, profibrotic, and carcinogenic stimuli. To protect the organism from these deleterious effects, the liver has evolved a number of defense systems, which include antioxidant substrates and enzymes, anti-inflammatory tools, enzymatic biotransformation systems, and metabolic pathways. Recent Advances: One of the pivotal systems that evolved during phylogenesis was the heme catabolic pathway. Comprising the important enzymes heme oxygenase and biliverdin reductase, this complex pathway has a number of key functions including enzymatic activities, but also cell signaling, and DNA transcription. It further generates two important bile pigments, biliverdin and bilirubin, as well as the gaseous molecule carbon monoxide. These heme degradation products have potent antioxidant, immunosuppressive, and cytoprotective effects. Recent data suggest that the pathway participates in the regulation of metabolic and hormonal processes implicated in the pathogenesis of hepatic and other diseases. Critical Issues: This review discusses the impact of the heme catabolic pathway on major liver diseases, with particular focus on the involvement of cellular targeting and signaling in the pathogenesis of these conditions. Future Directions: To utilize the biological consequences of the heme catabolic pathway, several unique therapeutic strategies have been developed. Research indicates that pharmaceutical, nutraceutical, and lifestyle modifications positively affect the pathway, delivering potentially long-term clinical benefits. However, further well-designed studies are needed to confirm the clinical benefits of these approaches. Antioxid. Redox Signal. 35, 734-752.
Keywords: Carbon Monoxide; hemová oxygenasa (decyklizující); Heme Oxygenase (Decyclizing); biliverdin; Heme; hem; Liver Diseases; lidé; Biliverdine; Heme Oxygenase-1; oxid uhelnatý; hemoxygenasa-1; nemoci jater; Humans